Review of Indialis Peters & Edmunds 1970 (Ephemeroptera, Leptophlebiidae) - Kluge, Nikita (Zootaxa, 2025)
Larva, subimago, imagines of both sexes and eggs of Indialis badia Peters & Edmunds 1970 are redescribed based on imagines reared from larvae. New synonymy is established: Indialis badia Peters & Edmunds 1970 (= Indialis thirparapensis Muthukatturaja & Balasubramanian 2022, syn. nov.; Indialis payaswini Muthukatturaja & Balasubramanian 2022, syn. nov.; Indialis kannani Muthukatturaja & Balasubramanian 2022, syn. nov.; Indialis kodagi Muthukatturaja & Balasubramanian 2022, syn. nov.). Based on imagines reared from larvae, larva, subimago, female imago and egg of Indialis rossi Peters 1975 are described for the first time, and male imago of this species is redescribed.